The Wall as Boundary, Edge and Identity Frontier: The Case of Offa’s Dyke - Villarreal Cabello, Víctor (2025)
This research examines Offa’s Dyke as a historical and symbolic artifact that functioned as a boundary, edge, and frontier, territorial, political, and identitarian, within the context of the transition from Late Antiquity to the Middle Ages in the British Isles. The study focuses on a specific case within the broader framework of walls as strategies of spatial control. Using a qualitative historical-documentary approach, it explores how a wall built in the 8th century by the Anglo-Saxon kingdom of Mercia not only physically demarcated the territory from the Brythonic peoples of the southwest, but also decisively contributed to the differentiated construction of two political identities that would later evolve into the nations of England and Wales. The study seeks to fill a gap in the existing literature on ancient borders and argues that Offa’s Dyke represents a crucial precedent for understanding contemporary dynamics of territorial delimitation and the formation of political subjectivities.